(untitled) (Международный научный журнал «Инженер», 2026)
This article provides a comprehensive overview of the modern theoretical foundations, classification, physicochemical and rheological properties, as well as the electrokinetic and kinetic characteristics of disperse systems, including the mechanisms of their formation and stabilization. The role of disperse systems in hydrotransport, along with the impact of their interaction with polymer composites on pressure dynamics, is analyzed based on international scientific research. The article covers both theoretical and practical approaches aimed at enhancing the significance of disperse systems in construction, mining, environmental protection, the food industry, and the oil and gas sectors.